The Feasibility Of Implementing The United Nations Guiding Principles On Business And Human Rights In The Extractive Industry In Nigeria - Abe, Oyeniyi (Journal of Sustainable Development Law and Policy, 2025)
Extractive resource governance has been a challenging task for resource-rich countries in Africa. It has fuelled civil wars, ethnic clashes and underdevelopment in this region. This has turned the so-called resource wealth into resource curse. To address this particularly nauseating challenge, the international community came together to adopt the UN Guiding Principles on Business and Human Rights (GPs). Polarised debate on whether the GPs should be binding or voluntary has slowed down the effective implementation of the Principles. This article argues that while the GPs have been the latest attempt at regulating multinational companies (MNCs), greater emphasis should be placed on the readiness of states to domesticate the Principles. To achieve this, the paper explores various approaches through which the GPs can be crafted into national legislation. It also investigates the different methods through which states can ensure that corporations systemically respect human rights obligations in their areas of operation. In order to restore faith in the whole process, it is necessary to examine how human rights principles can be mainstreamed into corporate practice locally. No doubt, rights-based frameworks, such as the GPs, are needed to ensure that human rights are streamlined in business’ projects, policies, and agreements throughout the various stages, including preparation, funding, implementation and monitoring. The issue of corporate liability under international law has had its troubled history, thus, this article argues that MNCs have a heightened responsibility to respect the human rights of the local communities in resourcerich, war-torn zones, particularly in sub-Saharan African, using Nigeria as focal point.